Excited States of Light-Harvesting Systems Based on Fullerene/Graphene Oxide and Porphyrin/Smaragdyrin - Cardenas-Jiron, G; Borges-Martinez, M (American Chemical Society, 2017)
In this work, we present a theoretical study at the density functional theory (DFT) level and time-dependent DFT of the ground and singlet excited states of electron donor-acceptor complexes formed by porphyrin (TPP)/smaragdyrin (TPOS) (expanded porphyrin), as light-harvesting systems, and fullerene (C60)/graphene oxide (GO), as acceptor nanocarbon structure. We investigate the effect of the nanocarbon on UV-vis electronic absorption of porphyrin/smaragdyrin, using the functionals B3LYP, PBE, M06, and wB97XD. The results showed the lowest deviation of the Q-band for the functional M06 (0.01-0.02 eV). Electronic absorption spectra calculated for the complexes with M06 predict that (a) graphene oxide increases the intensity of the Soret band, (b) fullerene produces a red-shift of the Q bands (4 nm) with respect to graphene oxide, and (c) smaragdyrin causes a red-shift of Q (27-48 nm) and Soret (37 nm) absorption bands as compared to porphyrin. We also investigate the effect of the nanocarbon structure on the charge-transfer (CT) excited states. Using the perturbative delta-SCF method with the PBE functional, we found that the charge-transfer excitation energy increases as TPOS-C60 (2.53 eV) < TPP-GO (2.89 eV) < TPP-C60 (3.01 eV) < TPOS-GO (3.28 eV). The presence of a nanocarbon structure affects more strongly smaragdyrin (∼0.8 eV) than porphyrin (∼0.1 eV). We show that the binding between smaragdyrin and fullerene C60 favors the charge separation states with a lower energy cost, which means that these systems present an advantage for its application in photovoltaic cells. (Figure Presented). © 2017 American Chemical Society.